The El Niño - Southern Oscillation, rainfall and wheat yields in South Africa - Begley, Paul (Department of Oceanography, 2016)
This thesis assesses the relationships between the El Niño-Southern Oscillation (ENSO), rainfall and South African commercial winter wheat yields from 1974 - 2000. The analysis is through a combination of the Pearson's product moment correlation coefficient and an assessment of the magnitude and consistency of rainfall and wheat anomalies in the year of, and the year following warm (El Niño) and cold (La Niña) ENSO events. The ENSO - rainfall relationship is analysed on timescales from 1 - 24 months and this study finds that there are more unusually dry and unusually wet months during El Niño events than during La Niña episodes (where dry and wet months are <75% and over 25% more than the 1921 - 2000 mean, respectively) and these conditions are consistently found in some rainfall areas during each El Niño or La Niño event; there is marked inter - El Niño and inter La Niña variation in late summer and annual rainfall; and that there has been a significant shift in the timings of maximum rainfall anomalies during El Niño episodes from an earlier investigation. The effects of rainfall on the wheat yield vary spatially, but are most apparent in the Free State where severe droughts have resulted in reduced yields. In the Northern Cape and Western Cape anomalously wet conditions, especially in late summer, coincide with reduced wheat yields. The ENSO - wheat yield relationship is not a simple linear one, and despite yields in the Northern Cape and Western Cape tracking Pacific sea surface temperatures by nearly a year, El Niño and La Niña years are not synonymous With increased or decreased yields in any province. ln fact, maximum and minimum yields in the Free State and Northern Cape are found in the year of, or year following a La Niño event, and consequently the present predictability of wheat yields by ENSO is limited. The relationships between ENSO, rainfall and wheat yield in South Africa is not readily apparent, which may be due to the short (<30 years) data set or mediating factors outside this study such as farm - management strategies or hemispheric variation in the evolution of El Niño and La Niña events.